1990
DOI: 10.1111/j.1365-2958.1990.tb00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of His residues in Bacillus subtilis cytochrome b558 for haem binding and assembly of succinate: quinone oxidoreductase (complex II)

Abstract: Cytochrome b558 in the cytoplasmic membrane of Bacillus subtilis constitutes the anchor and electron acceptor to the flavoprotein (Fp) and iron-sulphur protein (Ip) in succinate:quinone oxidoreductase, and seemingly contains two haem groups. EPR and MCD spectroscopic data indicate bis-imidazole ligation of the haem. Apo-cytochrome was found in the membrane fraction of haem-deficient B. subtilis, suggesting that during biogenesis of the oxidoreductase the cytochrome b558 polypeptide is embedded into the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…The ligand histidine residues have been identified in the primary sequence of the B. subtilis and E. coli SQR anchor polypeptides by site directed mutagenesis analysis [12,16,17]. These residues are located in predicted transmembrane segments as shown in Fig.…”
Section: The Cytoehrome B Componentmentioning
confidence: 99%
“…The ligand histidine residues have been identified in the primary sequence of the B. subtilis and E. coli SQR anchor polypeptides by site directed mutagenesis analysis [12,16,17]. These residues are located in predicted transmembrane segments as shown in Fig.…”
Section: The Cytoehrome B Componentmentioning
confidence: 99%
“…Discussion 1600 nm [14,16]. Moreover, mutagenesis studies of specific histidine residues in B. subtilis cytochrome b558 have identified four The primary objectives of this work was twofold: to establish histidines in hydrophobic segments that are essential for heme the axial ligation of cytochrome b560 in SQR and to investigate ligation and correct assembly of SQR [30]. Hence the available the origin of the changes in properties of this prosthetic group mutagenesis data provides additional support for a His/His that accompany isolation of the QPs.…”
Section: K and 5 T) In Sqr And Is Broadened And Shifted To 1535mentioning
confidence: 99%
“…A combination of EPR and near-infrared MCD spectroscopies [12] have shown that each of the heroes associated with the hydrophobic subunit (cytochrome b55s) of this enzyme has bis(histidine) ligation [11]. Subsequent site-directed mutagenesis studies have resulted in a postulated model in which specific histidines within this subunit have been assigned to the cytochrome components [10]. The data in this paper show that the single protoheme component of the E. coli succinate dehydrogenase also has bis(histidine) ligation.…”
Section: Introductionmentioning
confidence: 99%
“…the heme ligands within this family of enzymes have been those with the succinate dehydrogenase from B. subtilis [10,11]. A combination of EPR and near-infrared MCD spectroscopies [12] have shown that each of the heroes associated with the hydrophobic subunit (cytochrome b55s) of this enzyme has bis(histidine) ligation [11].…”
Section: Introductionmentioning
confidence: 99%